1964
DOI: 10.1002/lipi.19640661115
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bildung und Beseitigung verschiedener Steroid‐Derivate während der Raffination der Speiseöle

Abstract: In der vorliegenden Arbeit wird nachgewiesen, daO beim normalen, industriellen RaffinationsprozeD der Pflanzenole wesentliche Anderungen in der Zusammensetzung der Steroide eintreten. Bei der Raffination entstehen Autoxydationsprodukte dcr Steroide und daraus Sterin-Kohlenwasserstoffe. Es bilden sich Umwandlungsprodukte der Sterine, die in natiirlichen unbehandelten Pflanzenolen nicht vorkommen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1966
1966
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Smith (1981) reported the formation of colest-2,4,6triene (VIa) among the degradation products of 7-hydroperoxy and 7-hydroxy derivatives of cholesterol. The formation of steroidal hydrocarbons and ketosteroids from 7-hydroxy derivatives of β-sitosterol (IIb, IIIb) treated with bleaching earths was also reported long ago by Niewiadomski et al (1964) and by Kaufman et al (1970). Bortolomeazzi et al (1996) demonstrated the correlation between the oxidation products of β-sitosterol, campesterol, and stigmasterol and the formation of compounds with three double bonds in the ring system.…”
Section: Introductionmentioning
confidence: 61%
“…Smith (1981) reported the formation of colest-2,4,6triene (VIa) among the degradation products of 7-hydroperoxy and 7-hydroxy derivatives of cholesterol. The formation of steroidal hydrocarbons and ketosteroids from 7-hydroxy derivatives of β-sitosterol (IIb, IIIb) treated with bleaching earths was also reported long ago by Niewiadomski et al (1964) and by Kaufman et al (1970). Bortolomeazzi et al (1996) demonstrated the correlation between the oxidation products of β-sitosterol, campesterol, and stigmasterol and the formation of compounds with three double bonds in the ring system.…”
Section: Introductionmentioning
confidence: 61%
“…In particular, bleaching with acidic earths and deodorization at high temperatures can cause major changes, which are related to the conditions used, to the minor components present in the unsaponifiable matter of oils. In the case of sterols, isomerization with a shift of the double bonds and dehydration with formation of steroidal hydrocarbons (steradienes) and disteryl ethers have been reported (1)(2)(3)(4)(5)(6)(7)(8). The analysis of steradienes represents, in fact, a useful method for detecting the addition of refined oil to extra virgin olive oils and is one of the official methods in the European Union (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known of the fate of sterol oxides eventually present in the oil during the refining processes (Niewiadomski et al, 1964;Grob et al, 1994;Bortolomeazzi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterols can undergo transformation during the refining process of oils with the formation of isomers and dehydrated products (Niewiadomski et al, 1966;Grob et al, 1994;Mennie et al, 1994), which in turn can be analyzed to evaluate the quality of the oil and of other products (Lanzon et al, 1989;Cert et al,1994;Grob et al, 1995;Biedermann et al, 1996;Crews et al, 1997). Little is known of the fate of sterol oxides eventually present in the oil during the refining processes (Niewiadomski et al, 1964;Grob et al, 1994;Bortolomeazzi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%